Estimation of initial phenobarbital dosing in term neonates with moderate-to-severe hypoxic ischaemic encephalopathy following perinatal asphyxia - Šíma, M; Pokorná, P; Hartinger, J; Slanař, O (Journal of clinical pharmacy and therapeutics, 2018)
WHAT IS KNOWN AND OBJECTIVE: Phenobarbital is the first-line treatment of seizures in asphyxiated neonates; however, due to the high pharmacokinetic variability in this population, there is no consensus on the optimal dosage regimen. This study was conducted to identify variables that affect phenobarbital fate during routine clinical care and then to evaluate the dosage schedule that could be applied in term asphyxiated neonates with respect to achieving the target therapeutic range. METHODS: Phenobarbital pharmacokinetics was calculated based on serum concentrations measurements using one-compartmental model. Body weight, body surface area, gestational age, creatinine clearance, total bilirubin, alanine aminotransferase, aspartate aminotransferase, international normalized ratio, Apgar scores, umbilical cord arterial pH and base excess were explored as covariates in linear regression models. Based on this analysis, phenobarbital loading and maintenance dose regimen were projected. RESULTS AND DISCUSSION: In the whole study population (N = 36), phenobarbital volume of distribution, clearance and half-life median (interquartile range) values were 0.49 (0.38-0.59) L/kg, 0.0045 (0.0034-0.0055) L/h/kg and 75.1 (60.2-103.3) hours, respectively. The drug volume of distribution was associated with body weight, length and body surface area, whereas clearance was not in relationship with any explored features. Weight-normalized loading dose of 15 mg/kg and weight-normalized daily maintenance dose of 3 mg/kg proved to be optimal in our study population to reach phenobarbital therapeutic range. WHAT IS NEW AND CONCLUSIONS: This study presents basis for phenobarbital initial dosing in term asphyxiated neonates during first week of life. Phenobarbital weight-normalized loading dose of 15 mg/kg lead to simulated target peak concentrations in 72% of neonates, weight-normalized maintenance dose of 3 mg/kg lead to steady state within therapeutic window in the same proportion of patients.
Keywords: asfyxie; tkáňová distribuce; Male; Half-Life; retrospektivní studie; Hypoxia-Ischemia, Brain; fenobarbital; neonates; Tissue Distribution; gestační stáří; Gestational Age; dosing regimen; phenobarbital; mužské pohlaví; mozková hypoxie a ischemie; Asphyxia; novorozenec; Phenobarbital; lidé; ženské pohlaví; Humans; pharmacokinetics; asphyxia; Infant, Newborn; Retrospective Studies; Female; poločas